The Influence of Organizational Culture and Work Discipline on Productivity through Motivation - Muhammad Syahrum Alfan; Nor Lailla (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the direct and indirect effects of organizational culture and work discipline on employee productivity at PT Cahaya Engineering Sukses, with motivation as an intervening variable. Although the company has a strong organizational culture and relatively high work discipline, employee productivity remains below expectations, prompting an investigation into underlying factors such as social interaction, intrinsic motivation, and employee development. A quantitative correlational method was applied, with data collected from 92 respondents through structured questionnaires using a five-point Likert scale. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The findings reveal that both organizational culture and work discipline have significant and positive effects on productivity, with work discipline identified as the most influential factor. Motivation also plays a mediating role in linking organizational culture and work discipline to productivity. These results highlight that initiatives to strengthen culture and discipline should be supported by motivation-enhancing strategies to maximize performance. The study offers practical insights for integrated human resource development to boost organizational productivity effectively.